KAJIAN ISLAMOLOGI TENTANG TRADISI PEMBAHARUAN DAN MODERNITAS; TELAAH BUKU DIRASAT ISLAMIYAH HASSAN HANAFI - Rasyidi, Abdul Haris (JURNAL ISLAM NUSANTARA, 2017)
This study talks about the renewal of Muslim thought, especially in the study of Islamic sciences. In this book titled Dirasat Islamiyah, Hanafi tried to give the understanding of the renewal of thinking Muslims to Islam that is in modern times. It can be acknowledged that this Hanafi thought has an impact on the change of mind, especially in looking at the comparisons of Islamic thought in the East and other Islamic countries, especially those directly related to the occurrence of oxidalism (how Islam understands the concept of Western culture, thought and development.) This paper concludes Hanafi in reconstructing the minds of Muslims among others is to create a framework of the concept of thinking that is responsive to the development of the era.In addition, Hanafi also illustrates that Muslims do not think with conservative reasoning in seeing and answering the phenomenon that bind the Ummah. Muslims according to him, must be smart and courageous in taking steps and attitudes that would all be able to restore the glories of Islam that had lost by other thought and culture. He further illustrated the need for a reexamination of classical Islamic texts, as reference and references so that Muslims can formulate a responsive new Islamic concept, both in the form of Islamic thought and practice. The method used in this paper is the study of literature, by making direct source from Dirasat Islamiyah book and other sources related to the theme and the content of the writing.